Temelden Kliniğe COVID-19 - Toptan, Hande (Sakarya Üniversitesi Yayınları, 2023)
Since COVID-19 entered our lives, it has affected our social life, our working life, our lifestyle, our patient care services, our research, and even our behavioral style. Moreover, this epidemic has affected not only one country but also all countries of the world at the same time and with a similar intensity. Almost the health systems of the countries were tested with a test consisting of the same questions. During the pandemic, many unknown equations were intertwined. We had so many unknowns at the beginning of the epidemic. We did not yet clearly know how we approached patients, how to treat them, and what drugs should be given. Over the past two years, much research and many experiences have taught us how to behave against the disease. During the pandemic, we learned by experience how damaging information pollution can be. The epidemic also showed us the vaccine wars. We have seen how valuable the vaccines we use to get rid of the epidemic are, how developed countries have entered vaccine wars, and the change in the dynamics of the epidemic with vaccination. The years 2020-2022 will be defined as the epidemic years. During this epidemic, we saw that it was precious for physicians to get the correct information. This source has been tried to be created thanks to the fact that it has written down the experiences gained by experiencing this epidemic in person. We would like to express our sincere thanks to all our friends who contributed to the creation of the book. We hope this book will benefit readers.